Collins and Sivers asymmetries in muonproduction of pions and kaons off transversely polarised protons - C. Adolph; R. Akhunzyanov; M.G. Alexeev; G.D. Alexeev; A. Amoroso; V. Andrieux; V. Anosov; A. Austregesilo; B. Badełek; F. Balestra; J. Barth; G. Baum; et al. (Physics Letters B, 2015)
Measurements of the Collins and Sivers asymmetries for charged pions and charged and neutral kaons produced in semi-inclusive deep-inelastic scattering of high energy muons off transversely polarised protons are presented. The results were obtained using all the available COMPASS proton data, which were taken in the years 2007 and 2010. The Collins asymmetries exhibit in the valence region a non-zero signal for pions and there are hints of non-zero signal also for kaons. The Sivers asymmetries are found to be positive for positive pions and kaons and compatible with zero otherwise.